Analysis of Organizational Commitment and Leadership Style as Moderation Variables in Achieving Managerial Performance - Aida Nahar (Faculty of Economics Universitas Negeri Yogyakarta in collaboration with the Institute for, 2022)
AbstractThis study aims to analyze the moderating variables that affect the managerial performance of furniture companies in Jepara district. Managerial performance is achieved if the planning involves the participation of employees. Management and employees jointly design company plans. Therefore, this study examines whether budgetary participation affects managerial performance. In addition, the moderating variables of organizational commitment and leadership style were investigated in this study to strengthen the influence of budgetary participation on managerial performance. The population of this study was managers and employees of furniture companies in Jepara district, amounting to 77,817.The sampling technique was random sampling method and the technique of data analysis used moderated regression analysis. The result reveals that managerial performance is influenced by budgetary participation if there is organizational commitment and depends on the company's leadership style. Keywords: Budgetaryparticipation; Organizational commitment; Leadership style; and managerial performance Analisis Komitmen Organisasi dan Gaya Kepemimpinan Sebagai Variabel Moderasi dalam Pencapaian Kinerja Manajerial AbstrakPenelitian ini bertujuan untuk menganalisis variabel moderasi yang mempengaruhi kinerja manajerial perusahaan mebel di kabupaten Jepara. Kinerja manajerial tercapai jika perencanaan melibatkan partisipasi karyawan. Manajer dan karyawan bersama-sama merancang rencana perusahaan. Oleh karena itu, penelitian ini mengkaji apakah partisipasi penyusunan anggaran berpengaruh terhadap kinerja manajerial. Selain itu, komitmen organisasi dan gaya kepemimpian diteliti dalam penelitian ini untuk menguji apakah dapat memperkuat pengaruh partisipasi anggaran terhadap kinerja manajerialnya. Populasi dalam penelitian ini adalah manajer dan karyawan perusahaan mebel di kabupaten Jepara yang berjumlah 77.817 orang. Teknik pengambilan sampel menggunakan metode random sampling dan teknik analisis data menggunakan analisis regresi moderasi. Hasil penelitian ini adalah efektivitas bisnis dipengaruhi oleh partisipasi anggaran jika ada komitmen organisasi dan tergantung pada gaya kepemimpinan perusahaan Kata kunci: Partisipasi Anggaran, Komitmen Organisasi, Gaya Kepemimpinan, dan Kinerja Manajerial